Probable Cerebral Amyloid Angiopathy–Related Inflammation Associated With Sitravatinib: A Case Report. Issue 2 (April 2022) - Ray, Christopher; Dionne, Kalen
Abstract : Background and Objectives: We present the case of a 67-year-old man who developed encephalopathy, headaches, and seizure activity after initiating treatment with the novel tyrosine kinase inhibitor, sitravatinib. Methods: The patient was identified in routine clinical practice. Results: Brain MRI revealed lobar microhemorrhages and bihemispheric vasogenic edema. The patient met the criteria for probable cerebral amyloid angiopathy–related inflammation (CAA-ri) and responded favorably to high-dose methylprednisolone. Discussion: This report of neurologic autoimmunity in a patient receiving sitravatinib opens new lines of inquiry into the pathophysiology of CAA-ri. We emphasize the importance of early recognition and treatment of CAA-ri among patients receiving immunomodulatory chemotherapy.